Analysis of the main indicative values of the pharmaceutical market retail sectors in the constituent entities of the Russian Federation - I. К. Petrukhina; Т. К. Ryazanova; А. I. Khusainova; А. V. Egorova; P. R. Blinkova (IRBIS LLC, 2023)
Objective: to study various typological characteristics of the retail pharmaceutical market sector in 23 constituent entities of the Russian Federation (RF), as well as to analyze the availability of socially important types of pharmaceutical care as of 2021.Material and methods. The study materials were the data obtained on the basis of specially developed card-queries in the health authorities of constituent entities of the RF, and data from Rosstat, the Federal Antimonopoly Service of the RF, Roszdravnadzor. Methods of comparative, structural, logical and content analysis, as well as the method of data grouping were used. The study included analysis of the overall structure of retail sectors of regional pharmaceutical markets, the structure of pharmacy organizations (POs) depending on the form of ownership, availability of pharmaceutical care to the population of the RF constituent entities, and quantitative characteristics of POs that provide socially important types of pharmaceutical care: extemporaneous compounding of dosage forms, sales of drugs, psychotropic substances and their precursors included in the Lists II and III of the Decree No. 681 of the RF Government of June 30, 1998. Based on the obtained values of the indicative indicators, a typologization of the constituent entities of the RF was carried out.Results. By the total number of retail sales facilities the top five are regional pharmaceutical markets of Novosibirsk Region (2688), Nizhny Novgorod Region (2265), Samara Region (2493), Tula Region (1516), and Belgorod Region (1383). As of 2021, the share of pharmacies in the total pharmacy retail sector structure of the analyzed regions amounted to 45.5%, pharmacy outlets and kiosks - 54.1% and 0.4%, respectively. In most cases, the pharmaceutical market of constituent entities of the RF was concentrated: the mean value of the mean population per PO indicator was 2,215 persons. The pharmaceutical markets of Tula, Kursk and Pskov Regions are the most concentrated, the markets of Chechen Republic, Murmansk Region and Krasnoyarsk Territory are the least concentrated. The main burden of providing socially significant types of medicines falls on the state and municipal sectors, with the state sector accounting for 11.2% in the total structure of POs.Conclusion. Based on the study of basic indicators the situation in the pharmaceutical market retail sectors of different constituent entities of the RF was characterized. The revealed in 2021 downward trend in the total number of retail sales facilities may be caused by an excessively high degree of PO concentration on regional markets, as well as a noticeable reduction in the profitability of pharmaceutical activities (including due to a decline in the solvency of the population associated with the spread of a new coronavirus infection) and the impact of legislative changes.